Determination of the Stress Increase of the Unbonded Tendon in a Continuous Concrete Beam at Ultimate Capacity Using Nonlinear Analysis - Nakari Tarja; Laaksonen Anssi (Nordic Concrete Research, 2021)
Predicting the stress increase of an unbonded tendon in a post-tensioned continuous concrete beam at ultimate capacity is more difficult than when bonded tendons are used. The failure mechanisms of the continuous beam are also different to that of the simple-span beam. The loading type, ductility of the support area and moment redistribution influence the behaviour of the continuous structures. In this research, the simplified nonlinear analysis was used for predicting the unbonded tendon stress increase at ultimate capacity in continuous two-span beams. The model is based on the moment-curvature relationships of the reinforced concrete cross-sections under different compressive forces and deformations of the continuous beam under loading. The results have been compared with the experimental results of recent studies found in the literature. In addition, 92 unbonded post-tensioned two-span beams with different reinforcements have been examined by using the model and compared to the results obtained from empirical equations from the literature. The results from the nonlinear analysis correspond well to the results from the other models up to the reinforcement ratio of 0.35. The calculated values of the maximum moment capacity at the centre support were close to the results from the test beams.